(untitled) (Biological Sciences - PJSIR, 2010)
The 15 kV, cross-linked polyethylene (XLPE) insulated underground power cables, having polyethylene (PE) and polyvinyl chloride (PVC) jackets, were studied regarding the influence of moisture, chemicals and petroleum products. PE jackets were found to possess more suitable properties in harsh conditions and performed better than PVC jackets for use in electric power utilities, industry and other uses.